An examination of the effects of consumer ethnocentrism, consumer internationalism and consumer cosmopolitanism toward products from China in Malaysia - Abdul Latif, Samshul Amry; Abdul Talib, Asmat Nizam; Saad, Mazni; Sahar, Rafidah; Matyakubov, Umidjon (Taylor & Francis, 2024)
This study examines the effects of consumer ethnocentrism, consumer internationalism, and consumer cosmopolitism on Malaysians’ purchasing of electrical and electronic products from China. A reconceptualized consumer ethnocentrism measurement scale was used to capture cognitive, affective, and behavioral dimensions that previous studies have ignored. A total of 555 consumers were sampled through online questionnaires distributed on social media and used Partial Least Squares Structural Equation Modelling to test the proposed model. The results show that consumer ethnocentrism has a significant negative effect on Malaysian consumers’ willingness to buy Chinese products. In contrast, consumer cosmopolitanism was rejected due to opposing path directions, and consumer internationalism was insignificant. Future research should examine multi-dimensional consumer ethnocentrism in other countries and products, and incorporate alternative measurements for consumer cosmopolitanism. The research recommends that managers consider multi-dimensional consumer ethnocentrism when strategizing to market international products, as it provides more depth than simply relying on consumer cosmopolitanism.